(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines Italian proverbs that express the themes of friendship and love, focusing on their antonymic correlations through lexical and semantic analysis. The study explores how these proverbs encapsulate contrasting perspectives on relationships, highlighting both positive and negative aspects of friendship and love. By comparing these proverbs with their Uzbek equivalents, the research identifies cultural similarities and differences in proverbial wisdom. Furthermore, the study discusses translation challenges and the extent to which semantic equivalence can be maintained across languages. The findings demonstrate that proverbs not only reflect linguistic structures but also embody cultural values and societal norms.